Kompetensi guru sekolah menengah dalam mereka bentuk rancangan pengajaran - Haidir, Haidir (2016)
A good teaching requires a systematic planning. A systematic planning requires teachers that have a competence to design the lesson plan. Various efforts have been carried out by the government to improve the quality of the lesson plan. However, the efforts seem to be difficult to achieve if the teachers do not possess the required competencies to design a good lesson plan. The purpose of this study is to identify the competencies required in order to design the lesson plan in South Sulawesi, Indonesia. The study was conducted through mixed method using qualitative and quantitative techniques with exploratory sequential strategy. Six Educational Supervisors (Inspectors) and six Core Teachers (expert teachers) were interviewed to obtain information about the competencies needed for teachers in designing the lesson plan. The interview data were analyzed using thematic analysis and were used to develop a questionnaire. There were 400 teachers at Junior High School (SMP) and Senior High School (SMA) in South Sulawesi responded to the questionnaire on the competencies needed in designing the lesson plan. The questionnaire data were analyzed using Statistical Package for the Social Science (SPSS) software. The findings showed that there are four competencies needed for the secondary school teachers in designing a lesson plan. The competencies are firstly, an aspect of subject understanding with two dimensional namely concept and structure; secondly, an aspect of pedagogical knowledge with three dimensions, which are the organization of teaching, contextual knowledge, and the characteristics of students; thirdly, an aspect of Information Communication Technology (ICT) knowledge with two dimensions, which includes content appropriateness and student appropriateness; and fourthly, an aspect of the curriculum knowledge with two dimensions that are other subjects and taught subject. Analysis showed that there were no significant difference between teachers of Indonesian language, English, Mathematics, Sciences (IPA) and Social Studies (IPS) in SMP and SMA towards the required competence in designing the lesson plan. The study also discovered that there were no significant differences among SMP and SMA teachers in urban and rural areas towards the required competence in designing the lesson plan. The multiple regression analysis revealed that the aspect of the curriculum knowledge contributed 47.7% towards the competencies needed for secondary school teachers in designing the lesson plan. The knowledge of ICT contributed 13.7%, whereas the pedagogical knowledge contributed 7.7%, and aspect of subject understanding contributed 1.7%. The study proposes a framework of competencies needed by teachers in designing the lesson plan as guidance and reference for educational institution.